The Perception on Fundamentals of Online Courses: A Case on Prospective Instructional Designers - Genc, Zulfu; Tinmaz, Hasan (Acad Publisher House Researcher, 2016)
This study focuses on prospective instructional designers' perception toward creating online courses including which elements are essential for developing such platforms. The study is significant for revealing what the prospective instructional designers focus on while they design certain learning opportunities. The participants of the study were the Computer Education and Instructional Technology (CEIT) students from a university in Turkey (n=133) ranging from freshman to senior grades. Since the study aimed to obtain data to determine specific characteristics of a group, a non-experimental survey research design was employed. The participants were asked to assess the importance of fifteen online course elements (such as texts and videos). Afterwards, the participants were provided with seventeen sentences to reveal their thorough perceptions toward designing online courses. The study identified that the participants value feedback mechanism (M=4.69) at the most. The participants believed that the type of web browsers (M=4.50), the course login system (M=4.48), emailing tools (M=4.42), texts (M=4.32) and pictures (M=4.22) are fundamental elements of any online course. The study revealed that prospective instructional designers for online platforms were furnished themselves with the essence of offering online instructional activities. In this study as an example of gender related study, the significant differences on study items were found between males and females participants in terms of their perceptions on online courses. The results showed that voice mechanism was more important for female participants than male and female participants were logically-oriented and visual learners' during the entire online session.
Keywords: Distance education; Online course; Instructional design; Online tools; Student perception